Lightweight flame-retardant nano cellulose film as well as preparation method and application thereof

By chemically bonding flame-retardant elements to nanocellulose separators and performing in-situ polymerization to form a stable three-dimensional composite framework, the problems of insufficient thermal stability and flame retardancy of lithium-ion battery separators are solved, thereby improving the safety and high-rate performance of the battery.

CN121270985APending Publication Date: 2026-01-06HUNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511678381.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2026-01-06

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators suffer from insufficient thermal stability, poor flame retardancy, and poor electrolyte wettability, resulting in inadequate high-rate performance and safety.

Method used

Flame retardant elements are uniformly dispersed in the three-dimensional network structure of nanocellulose through chemical bonding, and combined with in-situ polymerization reaction to form a three-dimensional composite skeleton with both mechanical stability and flame retardant function, while retaining the porous structure and electrophilic properties of nanocellulose.

Benefits of technology

It significantly improves the safety and cycle stability of lithium-ion batteries, increases battery capacity and rate performance, and avoids the risks of uneven filler dispersion and thermal shrinkage short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121270985A_ABST
    Figure CN121270985A_ABST
Patent Text Reader

Abstract

The invention discloses a light flame-retardant nano cellulose film as well as a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The method comprises the following steps: mixing nanocellulose with a flame-retardant element source containing acid radicals, and carrying out hydrogen bond bonding and electrostatic interaction to obtain nanocellulose dispersion liquid rich in flame-retardant acid radicals; an oxidizing agent and a polymer monomer are added into the nanocellulose dispersion liquid rich in flame-retardant acid radicals for a polymerization reaction, and the nanocellulose film is obtained through suction filtration and film forming. The flame-retardant elements in the film are uniformly dispersed in the three-dimensional network structure in a chemical bonding manner, so that the thermal stability and the body flame retardance of the cellulose material can be improved, and the ionic conduction capability of the film can be improved by utilizing the porous structure of the nano cellulose material; when the material is applied to a lithium ion battery as a diaphragm material, the capacity and the rate capability of the battery can be improved, and the safety and the cycling stability of the battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, and relates to a lightweight flame-retardant nanofiber film, its preparation method and application. Background Technology

[0002] The separator is one of the four main materials in lithium-ion batteries, playing a crucial role in the physical isolation of the positive and negative electrodes and the transport of lithium ions. Its microporous structure and thermal stability significantly affect the battery's power output, cycle life, and safety characteristics. Currently, polyolefin (PP / PE) microporous membranes have become commercially available lithium-ion battery separators due to their good electrochemical stability, controllable thickness, and good mechanical strength. However, the poor electrolyte wettability of the PP / PE matrix leads to increased interfacial ion transport impedance, limiting the battery's high-rate performance. More seriously, when the battery is charged and discharged at high rates, the local heat accumulation in the battery can cause severe thermal shrinkage of PP / PE, easily leading to internal short circuits and even triggering thermal runaway reactions. Therefore, it is essential to develop high-safety separators with good electrolyte wettability, excellent heat resistance, and flame retardancy to improve the rate performance and safety stability of lithium-ion batteries.

[0003] Currently, some technologies directly employ the physical incorporation of flame-retardant particulate materials into separator materials to improve their thermal stability. For example, Chinese patent CN114284636A prepares a flame-retardant composite battery separator by physically introducing phosphorus (P) flame retardants through surface coating on an organic polymer base film or by doping during the preparation of the organic polymer base film. Similarly, Chinese patent CN117578032A discloses a flame-retardant cellulose separator composed of a cellulose membrane as the matrix, with carbon-coated nano-zinc oxide particles and a binder coating one side of the cellulose membrane. However, the above methods all suffer from pore blockage caused by uneven filler dispersion, leading to uneven lithium-ion distribution and transport. They also suffer from localized heat accumulation in the battery, causing the filler to detach from the matrix at high temperatures, exacerbating the risk of thermal shrinkage and short circuits. Therefore, the method of directly using particulate materials containing flame-retardant elements to improve the thermal stability of the separator has limitations.

[0004] Nanocellulose possesses papermaking and film-forming properties, exhibiting excellent film porosity and electrolyte wettability, which makes it possible to design high ion transport membranes. However, the inherent flammability of cellulose and its tendency to dehydrate and carbonize at high temperatures result in insufficient thermal stability and flame retardancy. Furthermore, its surface rich in polar hydroxyl groups may lead to interfacial side reactions in long-term electrochemical environments, limiting its safe use under high voltage and extreme operating conditions.

[0005] Therefore, how to effectively improve the flame retardancy and thermal stability of nanocellulose without sacrificing its inherent advantages, and suppress interfacial side reactions, to replace PP / PE separators and meet the key requirements of next-generation high-safety, high-energy-density battery separators, has become a key challenge in the current development of lithium-ion battery separator technology. Summary of the Invention

[0006] To address the problems of poor thermal stability of PP / PE membranes, insufficient heat resistance and poor structural stability of novel cellulose membranes in existing technologies, the first objective of this invention is to provide a lightweight flame-retardant nanofiber film in which flame-retardant elements are uniformly dispersed in a three-dimensional network structure through chemical bonding. This not only improves the thermal stability and bulk flame retardancy of the material, but also enhances the ion conductivity of the film by utilizing the porous structure of nanocellulose materials.

[0007] The second objective of this invention is to provide a method for preparing a lightweight flame-retardant nanofiber film. This method uses a synergistic approach of chemical modification and in-situ polymerization to enhance the tight bond between flame-retardant elements and nanocellulose and polymer monomers, achieving a uniform distribution of flame-retardant elements while retaining the electrophilicity, lightweight nature, and porous structure of nanocellulose.

[0008] The third objective of this invention is to provide an application of a lightweight flame-retardant nanofiber film as a separator material in lithium-ion batteries, which can improve the battery's capacity and rate performance, while also significantly enhancing the battery's safety and cycle stability.

[0009] To achieve the above-mentioned technical objectives, the present invention provides a method for preparing a lightweight flame-retardant nanofiber film. The method involves mixing nanocellulose with a flame-retardant element source containing acid radicals to achieve hydrogen bonding and electrostatic interaction, thereby obtaining a nanocellulose dispersion rich in flame-retardant acid radicals. An oxidant and polymer monomer are added to the nanocellulose dispersion rich in flame-retardant acid radicals to carry out a polymerization reaction, and the film is obtained by filtration.

[0010] In the technical solution of this invention, the flame-retardant element source containing acid radicals first undergoes esterification or hydrogen bonding with the hydroxyl groups on the nanocellulose molecular chain, thereby achieving the binding of the flame-retardant element with the cellulose molecules through chemical bonding or strong intermolecular forces. This step not only provides stable chemical anchoring sites for subsequent film formation but also achieves uniform loading of flame-retardant acid radicals on the surface of nanocellulose, effectively preventing the aggregation and migration of flame-retardant components. Subsequently, in the in-situ polymerization stage, the pre-added polymer monomers diffuse within the three-dimensional porous network formed by nanocellulose and undergo polymerization reactions with the acid radical modification sites under the initiation of an oxidant. The acid radical groups can act as chemical bonding centers in this process, promoting the connection between the polymer chain and nanocellulose. At the same time, a small or trace amount of polymer monomers polymerize around the acid radicals, coating and fixing sufficient flame-retardant acid radical ions on the surface of nanocellulose, thereby synergistically crosslinking to form a three-dimensional composite framework with both enhanced mechanical stability and flame-retardant function. In this process, the porosity, lightweight, and electrophilic properties of nanocellulose are preserved, ultimately achieving a simultaneous improvement in flame-retardant performance and thermal stability.

[0011] Experiments have shown that if the preparation method of the present invention does not adopt a stepwise approach, but instead allows hydrogen bonding, electrostatic interaction, and polymerization to proceed simultaneously, the polymer monomers will preferentially polymerize on the surface of nanocellulose, preventing sufficient flame-retardant acid radicals from participating in the coating reaction, thus failing to achieve chemical fixation, which in turn leads to a decrease in the flame-retardant properties of the film material.

[0012] As a preferred embodiment, the polymer monomer includes at least one of pyrrole, thiophene, aniline, and acrylic acid derivatives.

[0013] As a preferred embodiment, the flame-retardant element source containing acid radicals contains the flame-retardant element P. Further, when the flame-retardant element is P, the present invention effectively reduces raw material costs while fully ensuring the flame-retardant performance of the material.

[0014] As a preferred embodiment, the flame retardant source containing acid radicals is at least one selected from phytic acid, phosphomolybdic acid, phosphotungstic acid, and ammonium polyphosphate, with a concentration of 1-30 mmol / L; the polymer monomer is at least one selected from aniline and pyrrole. Since aniline has better thermal stability than other monomers, the polymer monomer is further preferably aniline.

[0015] As a preferred embodiment, the mass ratio of the nanocellulose to the flame-retardant element source containing acid radicals is 1:(4~12). In this invention, the amount of the flame-retardant element source containing acid radicals should be excessive relative to the amount of nanocellulose. This not only ensures sufficient bonding between the flame-retardant element and the nanocellulose through the acid radicals, but also allows some of the acid radicals to be physically loaded onto the surface of the nanocellulose, thus preparing for the subsequent synergistic crosslinking of polymer monomers. Furthermore, if the amount of nanocellulose is too small, the porosity of the three-dimensional network structure of the film material will be too low, thereby reducing the ionic conductivity of the material.

[0016] As a preferred embodiment, the hydrogen bonding and electrostatic interaction occur over a period of 0.5–6 hours. Within the reaction time range selected in this invention, sufficient acid radical modification of the nanofibers can be achieved.

[0017] As a preferred embodiment, the oxidant includes ferric chloride and / or ammonium persulfate.

[0018] As a preferred embodiment, the polymerization reaction conditions are: a time of 0.5 to 4 hours, and a mass ratio of the flame-retardant acid-rich nanocellulose dispersion, oxidant, and polymer monomer between 80:(1 to 10):(1 to 10), where the flame-retardant acid-rich nanocellulose dispersion is based on the mass of the flame-retardant acid-rich nanocellulose. Since the polymer monomers selected in this invention have good conductivity, the amount of polymer monomers used in this invention should be as small as possible relative to the amount of the flame-retardant acid-rich nanocellulose dispersion in order to ensure the overall insulation performance of the material. More preferably, the mass ratio of the flame-retardant acid-rich nanocellulose dispersion, oxidant, and polymer monomer is 80:(8 to 10):(8 to 10).

[0019] As a preferred embodiment, after the film is formed by filtration, free acid and residual oxidant are removed by washing, and then dried to obtain the final lightweight flame-retardant nanofiber film.

[0020] As a preferred embodiment, the drying temperature is 60~120℃ and the time is 6~24h.

[0021] The present invention also provides a lightweight flame-retardant nanofiber film, which is obtained by the above preparation method.

[0022] As a preferred embodiment, the film material possesses a three-dimensional network structure, with the flame-retardant elements uniformly distributed within this structure. This film material retains the lightweight and porous network structure of nanocellulose while uniformly dispersing the flame-retardant elements within the three-dimensional network structure through chemical bonding. This not only improves the material's thermal stability, bulk flame retardancy, and ionic conductivity, but also avoids the pore blockage and filler detachment problems caused by uneven filler dispersion resulting from the physical introduction of flame-retardant element particles in existing technologies.

[0023] As a preferred embodiment, the film has a porosity of 40-80%, a pore size of 80-500 nm, and a thickness of 5-30 μm. The film material of the present invention has a higher porosity than the unmodified nanocellulose film, which is more conducive to improving ion transport capability.

[0024] Finally, this invention also provides an application of a lightweight, flame-retardant nanofiber film, which will be used as a separator material in high-safety lithium-ion batteries.

[0025] The key to the excellent flame retardant properties and high ionic conductivity of the nanofiber film of this invention in lithium-ion batteries lies in the combined effect of acid radicals, a three-dimensional porous structure, and flame-retardant elements. Specifically, the acid radicals in the film are uniformly loaded on the nanofiber cellulose, giving it extremely high lithium-ion affinity, thereby enhancing electrolyte wettability. Its three-dimensional network structure further increases lithium-ion transport capacity and high thermal stability, thus achieving uniform and rapid ion transport and improving the safety performance of the lithium-ion battery. Simultaneously, during battery operation, the acid radicals containing flame-retardant elements in the film can catalytically dehydrate and carbonize under thermal runaway or local overheating conditions, rapidly forming a flame-retardant carbonized protective layer to capture combustion free radicals. This significantly improves the limiting oxygen index, blocks heat and oxygen transfer, and inhibits separator shrinkage and electrode short circuits, thereby significantly improving battery safety and cycle stability.

[0026] Furthermore, when the lightweight flame-retardant nanofiber film is used as a separator material in lithium-ion batteries, lithium iron phosphate is used as the positive electrode and lithium hexafluorophosphate is used as the electrolyte.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The flame-retardant elements and acid radicals in the film of the present invention are introduced through chemical bonding, which enables the nanocellulose to catalytically dehydrate and char at high temperatures, forming a flame-retardant carbonized protective layer and capturing combustion free radicals. This significantly improves the limiting oxygen index and inhibits combustion. While retaining the porosity and excellent electrolyte wettability of nanocellulose, the flame retardancy and stability of nanocellulose are significantly improved. Furthermore, the introduction of acid radicals further enhances the electrolyte wettability of the nanofiber membrane, promotes lithium-ion transport, and improves the rate performance of lithium-ion batteries.

[0029] (2) Unlike cellulose, which relies on hydrogen bond networks to improve the mechanical strength of fiber films, the introduction of trace polymer monomers into the film of the present invention can synergistically crosslink with acid radicals in the three-dimensional network structure of nanofibers, anchoring and coating acid radical ions on the surface of nanocellulose to form a three-dimensional composite skeleton with both mechanical reinforcement and flame retardant functions, thereby improving the tensile strength and heat shrinkage resistance of the film.

[0030] (3) The preparation method of the present invention retains the electrolyte affinity, lightweight and porous structure of nanocellulose. It is simple to operate, green and environmentally friendly, and suitable for continuous production. It can be widely used in the preparation of separators and flame-retardant heat insulation layers for energy storage devices such as lithium-ion batteries, and is suitable for the use requirements of high-power and long-life batteries.

[0031] (4) The lightweight flame-retardant nanofiber film of the present invention can be used as a separator material to replace commercially available polyethylene (PE) / polypropylene (PP) battery separator materials that are prone to heat shrinkage and deformation, and can be applied to lithium-ion batteries, thereby improving the high-temperature cycle performance and safety of lithium-ion batteries. Attached Figure Description

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0033] Figure 1 These are optical images and scanning electron microscope (SEM) images of the lightweight flame-retardant nanocellulose film prepared in Example 1 of this invention; (a) is an optical image, and (b) is a scanning electron microscope (SEM) image.

[0034] Figure 2 Optical images and scanning electron microscope (SEM) images of polyaniline powder provided in Comparative Example 1 of the present invention are shown; (a) is an optical image, and (b) is a scanning electron microscope (SEM) image.

[0035] Figure 3 The images show a comparison of scanning electron microscope (SEM) images of the cross-section of the phosphate particle / nanocellulose composite film prepared in Comparative Example 3 of the present invention before and after immersion in a lithium-ion battery electrolyte for 12 hours; (a) before immersion, (b) after immersion.

[0036] Figure 4 The figures show the charge-discharge curves of the two separators of the present invention used in lithium-ion batteries at different rates; (a) is the charge-discharge curve of the flame-retardant nanocellulose battery separator of Example 1 of the present invention, and (b) is the charge-discharge curve of the commercial PE separator. Detailed Implementation

[0037] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0038] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0039] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0040] The nanocellulose powder used in the embodiments and comparative examples of this invention was purchased from Shandong Shengquan Group.

[0041] Example 1

[0042] This embodiment provides a method for preparing a lightweight flame-retardant nanofiber film, which specifically includes the following steps:

[0043] (1) Weigh 50 mg of nanocellulose powder and 200 mg of a mixture of phytic acid and phosphotungstic acid (wherein the mass ratio of phytic acid and phosphotungstic acid is 1:1) and add it to 50 mL of deionized water. Stir the mixture at room temperature for 30 min to obtain a nanocellulose dispersion rich in phosphate.

[0044] (2) Take 80 mg of the phosphate-rich nanocellulose dispersion prepared in step (1), add 10 mg of aniline monomer and 10 mg of ammonium persulfate as oxidant, stir at room temperature for 2 hours to carry out polymerization reaction, filter and wash directly to form a film, heat and dry in an oven, peel off to obtain a flame-retardant nanofiber film with a thickness of about 25 μm, a porosity of about 65%, and a smooth and dense surface.

[0045] The film showed no swelling after being immersed in conventional lithium-ion battery electrolyte for 12 hours, had a limiting oxygen index of 34%, and passed the flame retardancy test.

[0046] Example 2

[0047] The only difference between this embodiment and Example 1 is that the polymer monomer is replaced with an equal mass of pyrrole monomer, while the other conditions and steps are the same, resulting in a lightweight flame-retardant nanofiber film.

[0048] The film has a thickness of approximately 22 μm, a porosity of approximately 55%, and a smooth and dense surface. It showed no swelling after immersion in conventional lithium-ion battery electrolyte for 12 hours, exhibited a limiting oxygen index of 32%, and passed flame retardancy testing.

[0049] Example 3

[0050] The only difference between this embodiment and Embodiment 1 is that phytic acid and phosphotungstic acid are replaced with an equal mass of phosphomolybdic acid. All other conditions and steps are the same, resulting in a lightweight flame-retardant nanofiber film.

[0051] The film has a thickness of approximately 28 μm, a porosity of approximately 62%, and a smooth and dense surface. It showed no swelling after immersion in conventional lithium-ion battery electrolyte for 12 hours, exhibited a limiting oxygen index of 38%, and passed flame retardancy testing.

[0052] Example 4

[0053] The only difference between this embodiment and Example 1 is that the mass of aniline monomer is halved; all other conditions and steps are the same, resulting in a lightweight flame-retardant nanofiber film.

[0054] The film has a thickness of approximately 30 μm, a porosity of approximately 76%, and a smooth, flat surface. It showed no swelling after immersion in conventional lithium-ion battery electrolyte for 12 hours, exhibited a limiting oxygen index of 34%, and passed flame retardancy testing.

[0055] Comparative Example 1

[0056] The only difference between this comparative example and Example 1 is that nanocellulose powder is not added in step (1). All other steps and conditions are the same. After filtration, washing and drying, only loose polyphosphate powder is obtained, which cannot form a continuous self-supporting film.

[0057] Comparative Example 2

[0058] In this comparative example, only 50 mg of nanocellulose powder was weighed and added to 50 mL of deionized water for ultrasonic dispersion. The mixture was then directly filtered and dried to obtain a pure nanocellulose film with a thickness of approximately 22 μm.

[0059] The film changes from white to light yellow on the surface after 30 minutes at 200°C, with a limiting oxygen index of only 22%, which is insufficient to meet the flame retardant requirements for high-safety battery separators.

[0060] Comparative Example 3

[0061] The difference from Example 1 is that 10 mg of polyphosphate powder obtained in Comparative Example 1 was added to 50 mg of nanocellulose powder, 100 mL of water was added for ultrasonic dispersion, a vacuum filtration device was set up, and the mixture was directly filtered and dried to obtain a phosphate particle / nanocellulose composite film.

[0062] After being immersed in conventional lithium-ion battery electrolyte for 12 hours, the composite film of Comparative Example 3 showed significant swelling, with particles detaching from the nanocellulose, making it difficult to meet the requirement of stable cycling in the battery.

[0063] Comparative Example 4

[0064] The difference from Example 1 is that flame-retardant phosphoric acid is replaced with the same mass of sulfuric acid, while all other steps and conditions are the same.

[0065] Because sulfuric acid oxidizes the hydroxyl groups on cellulose, and sulfate ions easily migrate and precipitate during the drying process, a uniform and dense composite film cannot be obtained, resulting in a significant decrease in flame retardant effect.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that flame-retardant phosphoric acid is not used in the reaction system; instead, the polymer monomers are directly polymerized on the surface of nanocellulose. All other steps and conditions are the same, resulting in a polymer-nanocellulose film material.

[0068] The film material is about 20 μm thick, with a porosity of about 48%, which is relatively dense. Its limiting oxygen index is 26%, and its flame retardant effect is not good.

[0069] Figure 1 Image (a) shows a black, smooth, flame-retardant nanocellulose film. The flame-retardant nanocellulose film obtained in Example 1 was characterized by scanning electron microscopy, as shown... Figure 1 As shown in (b), the flame-retardant nanocellulose film has cross-linked fibers with a diameter of 130 nm, a large number of pores with a pore size of 80~500 nm, and the pores are uniformly distributed.

[0070] like Figure 2 As shown, without the participation of nanocellulose in the synthesis, the polyphosphate powder prepared in Comparative Example 1 consists of particles of varying sizes. Without a binder, a smooth, spreadable flame-retardant protective layer cannot be obtained; it can only be formed by… Figure 2 (a) shows that it exists in powder form.

[0071] like Figure 3 As shown, under the conditions of preparing a film by mixing nanocellulose and flame-retardant phosphate powder, the film powder particles obtained in Comparative Example 3 were randomly dispersed in nanofibers. After soaking in electrolyte for 12 hours, cracks appeared in the cross section of the film, indicating that there was swelling, which would damage the mechanical strength and ion transport performance of the membrane. It also shows that the effect of physically incorporating flame-retardant element sources containing acid radicals is significantly less than the chemical bonding method of the present invention.

[0072] The flame-retardant nanocellulose film obtained in Example 1 was used to replace the commercial P-type separator in a lithium battery, and its electrical performance was tested at 60°C. A lithium metal sheet was used as the negative electrode, lithium iron phosphate as the positive electrode, and a commercially available lithium hexafluorophosphate electrolyte was used. Specifically... Figure 4 As shown, where, Figure 4 The charge-discharge curve of the flame-retardant nanocellulose film obtained in Example 1, shown in (a), is compared with that of commercial PP separators. Figure 4(b) shows that in battery systems using lithium iron phosphate as the cathode, it has higher capacity and better rate performance.

[0073] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a lightweight flame-retardant nanofiber film, characterized by: The nanocellulose is mixed with a source of acid-containing flame-retardant elements to form hydrogen bond and electrostatic interaction, to obtain a nanocellulose dispersion liquid rich in flame-retardant acid radicals; an oxidizing agent and a polymer monomer are added to the nanocellulose dispersion liquid rich in flame-retardant acid radicals to perform a polymerization reaction, and a membrane is formed by suction filtration.

2. The method of claim 1, wherein the method is characterized by: The polymer monomer includes at least one of pyrrole, thiophene, aniline and acrylic derivatives.

3. The preparation method of the light-weight flame-retardant nanofiber film according to claim 1 or 2, characterized in that: The source of acid-containing flame-retardant elements contains flame-retardant element P.

4. The method according to claim 3, wherein the method is characterized by: The source of acid-containing flame-retardant elements is at least one of phytic acid, phosphomolybdic acid, phosphotungstic acid and ammonium polyphosphate, and the concentration is 1-30 mmol / L; and the polymer monomer is at least one of aniline and pyrrole.

5. The preparation method of the light-weight flame-retardant nanofiber film according to claim 1, characterized in that: The mass ratio of the nanocellulose to the source of acid-containing flame-retardant elements is 1:(4-12); The time of the hydrogen bond and electrostatic interaction is 0.5-6 h.

6. The method of claim 5, wherein the method is characterized by: The oxidizing agent includes ferric chloride and / or ammonium persulfate.

7. The method of claim 1, wherein the method is characterized by: The polymerization reaction is performed under the following conditions: the time is 0.5-4 h, the mass ratio of the nanocellulose dispersion liquid rich in flame-retardant acid radicals, the oxidizing agent and the polymer monomer is 80:(1-10):(1-10), and the nanocellulose dispersion liquid rich in flame-retardant acid radicals is based on the mass of the nanocellulose rich in flame-retardant acid radicals.

8. A lightweight flame-retardant nanofiber film, characterized by: The film is obtained by the preparation method according to any one of claims 1-7.

9. The lightweight flame-retardant nanofiber film according to claim 8, characterized in that: The film has a three-dimensional network structure, and the flame-retardant elements are uniformly distributed in the three-dimensional network structure. The film has a porosity of 40-80%, a pore size of 80-500 nm and a thickness of 5-30 μm.

10. The use of a lightweight flame-retardant nanofiber film according to claim 8 or 9, characterized in that: The film is applied as a separator material in a lithium ion battery.

Citation Information

Patent Citations

  • Flame-retardant composite battery diaphragm as well as preparation method and application thereof

    CN114284636A

  • Cellulose diaphragm for lithium metal battery as well as preparation method and application of cellulose diaphragm

    CN117578032A